(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
the rapid expansion of interactive digital platforms in higher education has changed not only the technical organization of teaching, but also the professional profile of the future educator. In contemporary pedagogical discourse, pedagogical mastery is no longer interpreted as a static set of rhetorical, methodological, and organizational skills acquired once and for all; rather, it is increasingly understood as a dynamic, reflective, ethically grounded, and technologically mediated capacity to design meaningful learning, sustain dialogue, diagnose difficulties, personalize support, and transform instructional situations into developmental opportunities. This article examines the scientific and methodological foundations for developing students’ pedagogical mastery through interactive platforms and argues that such development becomes effective only when technology is subordinated to pedagogical logic, dialogic interaction, and reflective practice. The study relies on integrative analysis of international conceptual frameworks, policy documents, and empirical research on digital pedagogy, online teaching competencies, mobile learning, learner engagement, and teacher professional development. On this basis, the article systematizes the conceptual approaches that should guide the educational use of interactive platforms in higher education, including competence-based, activity-oriented, constructivist, humanistic, reflective, and data-informed approaches. The article proposes a methodological model in which interactive platforms function not as repositories of content, but as environments for co-construction of knowledge, staged feedback, multimodal participation, collaborative inquiry, self-assessment, and pedagogical reflection. Special attention is devoted to the didactic conditions that ensure the transition from superficial digital activity to genuine pedagogical mastery: purposeful instructional design, ethical use of educational data, teacher facilitation, academic integrity, inclusive access, structured reflection, and continuity between theory and practice. The findings show that interactive platforms can substantially strengthen students’ pedagogical mastery when they are integrated into the curriculum as developmental ecosystems rather than as isolated technical tools, and when institutional support, educator competence, and assessment culture evolve in parallel.